Differing patterns in thermal injury incidence and hospitalisations among 0-4 year old children from England - Baker, Ruth; Tata, Laila J.; Kendrick, Denise; Burch, Tiffany; Kennedy, Mary; Orton, Elizabeth (Elsevier, 2016)
Objective: To describe patterns in thermal injury incidence and hospitalisations by age, sex, calendar year and socioeconomic status among 0-4 year olds in England for the period 1998-2013.